Nigeria : Poverty Reduction Strategy Paper; Progress Report. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses the progress report on the National Economic Empowerment and Development Strategy (NEEDS) for Nigeria. The NEEDS 2004-07 is Nigeria's reform based medium-term plan for economic recovery, growth, and development. Fiscal and monetary policies have been carefully managed in the implementation of NEEDS. A major budget reform introduced under NEEDS was the Oil Price Based Fiscal Rule and Medium Term Expenditure Framework (MFEF), which has enhanced macroeconomic stability by delinking government expenditure from the price of oil.